CryoEM at 100 keV: a demonstration and prospects. (2019) - Naydenova, K.; McMullan, G.; Peet, M. J.; Lee, Y.; Edwards, P. C.; Chen, S.; Leahy, E.; Scotcher, S.; Henderson, R.; Russo, C. J.
No abstract available